2016
DOI: 10.1136/bmjopen-2016-011630
|View full text |Cite|
|
Sign up to set email alerts
|

Hundred top-cited articles focusing on acute kidney injury: a bibliometric analysis

Abstract: BackgroundAcute kidney injury (AKI) is a major global health issue, associated with poor short-term and long-term outcomes. Research on AKI is increasing with numerous articles published. However, the quantity and quality of research production in the field of AKI is unclear.Methods and analysisTo analyse the characteristics of the most cited articles on AKI and to provide information about achievements and developments in AKI, we searched the Science Citation Index Expanded for citations of AKI articles. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 41 publications
(44 reference statements)
1
35
1
Order By: Relevance
“…The Critical Care Medicine journal published the largest number of highly cited articles. In another bibliometric analysis investigating the top 100 cited articles in acute kidney injury, Liu and colleagues found that the top 100 articles originated from 15 countries, led by the US (n=81) (8). This is consistent with our study that authors from the US published more than half of the most highly cited articles in general.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The Critical Care Medicine journal published the largest number of highly cited articles. In another bibliometric analysis investigating the top 100 cited articles in acute kidney injury, Liu and colleagues found that the top 100 articles originated from 15 countries, led by the US (n=81) (8). This is consistent with our study that authors from the US published more than half of the most highly cited articles in general.…”
Section: Discussionsupporting
confidence: 90%
“…The bibliometric studies can help to (I) identify hotspots in a certain area; (II) network connections between subspecialties; (III) the leading investigators; and (IV) author's scientific output. Many bibliometric studies focused on a few vital issues in the field of CCM such as sepsis, severe brain injury and acute kidney injury (6)(7)(8). However, to the best of our knowledge, there is no bibliometric study that analyzes the entire CCM area.…”
Section: Introductionmentioning
confidence: 99%
“…The number of citations for the 10 top‐cited articles in lithium toxicity varied from 211 to 79, which was less than those in other subspecialties in non‐toxicological fields and within the range of citations in other subspecialties in toxicological fields . Citations fluctuate in different subspecialties and depend on the research activity in certain field.…”
Section: Discussionmentioning
confidence: 97%
“…[25] Even though there are many publications on urological emergencies in current literature, there are very few bibliometric studies. [26] In this study, we conducted the bibliometric analysis of top 100 cited articles on urological emergencies since 1975 among 360 articles we obtained by using [27] We determined that the most cited article (467-fold cited) was "International Clinical Practice Guidelines for the Treatment of Acute Uncomplicated Cystitis and Pyelonephritis in Women: A 2010 Update by the Infectious Diseases Society of America and the European Society for Microbiology and Infectious Diseases" by Gupta et al [28] Citation numbers and being published in journals with high impact factors are important indicators of the quality of an article. Classically, it is not expected for the articles published in recent years to be cited as much as the older ones.…”
Section: Discussionmentioning
confidence: 99%
“…In another study Thomas et al [15] suggested that the most cited papers or classic papers in urology varied depending on the time period studied. In a bibliometric analysis on acute kidney injury by Liu et al [26] it was found that most of the clinical articles (55%) among the top 100 cited articles investigated patients with any cause of acute kidney injury, followed by the specific causes of contrast-induced acute kidney injury (25%) and cardiac surgery-induced acute kidney injury (15%) of the top 100 cited articles.…”
Section: Aetiologic/therapeuticmentioning
confidence: 99%